2017
DOI: 10.1515/mmcks-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management practices stimulating knowledge sharing

Abstract: Abstract. The major goal of the paper was to develop a theoretical framework that conceptualizes the indirect impact on human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 62 publications
(183 reference statements)
1
22
0
Order By: Relevance
“…Tacit knowledge is a type of knowledge that cannot be articulated or verbalized; it resides in an intuitive realm (Foos et al, 2006) but can be utilized effectively in work life. The study of Matošková and Směšná (2017) concluded that one of the basic dimensions of knowledge sharing in the organization are knowledge interactions. A knowledge interaction content is sharing or exchanging several tacit knowledge coming from a life-time experience of teamwork member that is easy to be explained but hard to be codified as explicit knowledge.…”
Section: Salespeople's Tacit Knowledge Exchange and Salespeople Innovmentioning
confidence: 99%
“…Tacit knowledge is a type of knowledge that cannot be articulated or verbalized; it resides in an intuitive realm (Foos et al, 2006) but can be utilized effectively in work life. The study of Matošková and Směšná (2017) concluded that one of the basic dimensions of knowledge sharing in the organization are knowledge interactions. A knowledge interaction content is sharing or exchanging several tacit knowledge coming from a life-time experience of teamwork member that is easy to be explained but hard to be codified as explicit knowledge.…”
Section: Salespeople's Tacit Knowledge Exchange and Salespeople Innovmentioning
confidence: 99%
“…Study on knowledge sharing has attracted scholars at least in this decade in exploring the nature, social role as well as its professional role, and the importance of knowledge sharing in enhancing performance (Aubke et al 2014, Ferdinand and Wahyuningsih 2018, Ghobadi 2015, Matošková and Směšná 2017, Mueller 2014, Nesheim and Hunskaar 2015, Nissen et al 2014, Wulandari et al 2018. Knowledge sharing within a teamwork members impacts on feeling of meaningfulness while information giving activity positively impacts on productivity (Aubke et al 2014).…”
Section: Knowledge Sharing In a Teamworkmentioning
confidence: 99%
“…Knowledge sharing or knowledge exchange between team member through the activity of Teaching each other in the team, pass on the learned knowledge and sharing of unsuccessful experience is recognized as tools for enhancing team member innovativeness leading for better performance (Ferdinand and Wahyuningsih 2018). One of the basic dimension in knowledge sharing process is interactions between members that may influenced by of impacted to motivation, attitude, knowledge, and skill (Matošková and Směšná 2017) leading to a better performance. Knowledge sharing between team is a vital to organization-wide learning which is driven by output orientation an openness in team members (Mueller 2014).…”
Section: Knowledge Sharing In a Teamworkmentioning
confidence: 99%
“…Knowledge management processes can be defined as all of the activities that are related to knowledge and carried in the organisations by internal or external parties. Knowledge management processes differ from one organisation to another and the number of these processes is not agreed upon among scientists (Liu et al, 2013;Wee & Chua, 2013;Obeidat et al, 2014;Ranjbarfard et al, 2014;Al Saifi, 2015;Chang & Lin, 2015;Sangari et al, 2015;Schenk et al, 2015;Suorsa, 2015;Tongo, 2015;Wahba, 2015;Kianto et al, 2016;Lee et al, 2016;Little & Deokar, 2016;Känsäkoski, 2017;Matoskova & Smesna, 2017;Pandey et al, 2018;Raudeliūnienė et al, 2018). Many researchers have studied different knowledge management processes, the most recent of them are classified according to (Table 1): creation, generation; sharing, transfer, distribution, dis-semination, conversion; application, reuse, interpretation; storage, codification, retention; acquisition, capture.…”
Section: Knowledge Management Processesmentioning
confidence: 99%
“…Knowledge management started to be known as a discipline in the beginning of 1990s (Pauleen & Wang, 2017) and over the years it became of interest to many scientists and practitioners who studied different areas related to knowledge management processes and their effect on the organisational performance (Massingham & Al Holaibi, 2017). Most researchers have recognized knowledge management as a crucial factor for organisations' success since it positively affects employees and customers satisfaction, and it is the main resource for increasing efficiency of the organisations' performance, which leads to building organisational uniqueness in the current dynamic environment (Cepeda-Carrion, Martelo-landroguez, Leal-Rodríguez, & Leal-Millán, 2017;Mageswari, Sivasubramanian, & Dath, 2017;Matoskova & Smesna, 2017;Alavijeh, Esmaeili, Sepahvand, & Davidavičienė, 2018).…”
Section: Introductionmentioning
confidence: 99%